Amém, camarada: religião e sociedade na trajetória de Helder Camara - Alves, Daniella Maria Cardoso de Brito (2011)
This dissertation sought to understand the different positions of Dom Helder Camara, beginning with his trajectory in the theory of Pierre Bourdieu, during his pastoral activity between the 1930 and 1990, focusing his activities in different contexts in his field and in relation to other subjects and social spheres.Through the analysis of speeches made by the priest during this period, this study analyzes the successive positions taken by this social agent, from fundamentalism in the 1930s, through liberation theology, the defense of freedom during the military dictatorship and the reaffirmation of Catholic identity as a factor for social action, in the end of his pastoral work. With similar trajectory to other Catholic leaders from his time, Helder Camara united something unique in life constant, and public, effort to, from the religion, articulate pastoral action in other areas of society.